1999
DOI: 10.1016/s0014-5793(99)01217-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of the relationship between low‐level chemiluminescence and lipid peroxides in oxidation of low‐density lipoprotein

Abstract: In this study oxidation of low-density lipoprotein (LDL) induced by different Cu 2+ concentrations was investigated. Lipid peroxidation was assessed by monitoring low-level chemiluminescence (LL-CL), conjugated diene hydroperoxide (CD) and K K-tocopherol (TocOH), the major lipophilic antioxidant in LDL. At high Cu 2+ concentration, LDL oxidation was characterised by CD formation, LL-CL emission and TocOH consumption. At low Cu 2+ concentration, CD formation was independent of LL-CL and occurred in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In particular, the oxidation of amino acids and proteins by peroxyl radicals (7,8), hypochlorite (9–11) or peroxynitrite (12,13) leads to CL emission in the visible region. Similar emissions are observed in the Cu(II), Fe(II) and peroxyl radical‐promoted oxidation of lipoproteins (14,15). From the time profile of the emission, as well as the response of the emitted intensity to the addition of free radical scavengers and compounds with peroxidase‐like activity, it has been concluded that this emission is due to the decomposition of peroxides and/or endoperoxides formed during the oxidation process (7–9,15,16).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In particular, the oxidation of amino acids and proteins by peroxyl radicals (7,8), hypochlorite (9–11) or peroxynitrite (12,13) leads to CL emission in the visible region. Similar emissions are observed in the Cu(II), Fe(II) and peroxyl radical‐promoted oxidation of lipoproteins (14,15). From the time profile of the emission, as well as the response of the emitted intensity to the addition of free radical scavengers and compounds with peroxidase‐like activity, it has been concluded that this emission is due to the decomposition of peroxides and/or endoperoxides formed during the oxidation process (7–9,15,16).…”
Section: Introductionsupporting
confidence: 61%
“…Similar emissions are observed in the Cu(II), Fe(II) and peroxyl radical‐promoted oxidation of lipoproteins (14,15). From the time profile of the emission, as well as the response of the emitted intensity to the addition of free radical scavengers and compounds with peroxidase‐like activity, it has been concluded that this emission is due to the decomposition of peroxides and/or endoperoxides formed during the oxidation process (7–9,15,16). The thermal decomposition of these intermediates would lead to the formation of the excited carbonyls responsible of the emitted CL (7,9).…”
Section: Introductionsupporting
confidence: 61%
“…As a consequence of unsaturated lipids doublebonds oxidation, peroxide radicals are generated (LOO * ). Reactions between peroxide radicals leads to the formation of products in the electronic excitation state (L = O * ), which are able to emit light [3][4][5]. The reaction is as follows:…”
Section: Introductionmentioning
confidence: 99%
“…The xanthine/xanthine oxidase system (Sigma) was added several times to the same sample, which was spectrophotometrically monitored to check its absorbance at 500 nm [19][20][21].…”
Section: Study Of the Effects Of Radicals Produced By Xanthine/xanthimentioning
confidence: 99%
“…This cascade of radical reactions results in a final partial recombination of lipid peroxyl radicals to form a nonradical product; this reaction is accompanied by a photoemission that can activate rhodopsin and may lead to the perception of light [18][19][20][21] in humans and other vertebrates. It has been reported that this emission has a spectrum with a maximum between 420 and 500 nm, which is coincident with that of retinal [22].…”
Section: Introductionmentioning
confidence: 99%